2002
DOI: 10.2118/75805-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Reservoir Simulator for Large-Scale Reservoir Simulation

Abstract: A new parallel, black-oil-production reservoir simulator (Powers**) has been developed and fully integrated into the pre-and post-processing graphical environment. Its primary use is to simulate the giant oil and gas reservoirs of the Middle East using millions of cells. The new simulator has been created for parallelism and scalability, with the aim of making megacell simulation a day-to-day reservoir-management tool. Upon its completion, the parallel simulator was validated against published benchmark proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Parallel processing with high performance computing clusters can alleviate these challenges to a good extent. Wang et al (1997), Zhang et al (2001), Dogru et al (2002), Gai et al (2003), andDeBaun et al (2005) demonstrated the necessity, advantages, and applicability of using parallel processing for large-scale reservoir simulations.…”
Section: Parallel Processingmentioning
confidence: 99%
“…Parallel processing with high performance computing clusters can alleviate these challenges to a good extent. Wang et al (1997), Zhang et al (2001), Dogru et al (2002), Gai et al (2003), andDeBaun et al (2005) demonstrated the necessity, advantages, and applicability of using parallel processing for large-scale reservoir simulations.…”
Section: Parallel Processingmentioning
confidence: 99%
“…Many reservoir simulators have been developed by different companies, universities and research centers. The majority of them are commercially available or have been presented in the literature [3]- [10]. Regardless of how precise these simulators are, the uncertainties in the measured reservoir characteristics which are used as their inputs may cause errors in the production forecast [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980s, various of parallel simulators were developed (Li et al, 1995;Wheeler and Smith, 1989;Rutledge et al, 1991;Shiralkar et al, 1997;Parashar et al, 1997;Kaarstad et al, 1995;Killough and Bhogeswara, 1991;Killough et al, 1997). In (Dogru et al, 2002(Dogru et al, , 2009), Dogru et al developed a parallel simulator, GigaPOWERS, which has been successfully applied to a case with one billion gird cells, and a truncated Neumann series preconditioner is developed. In (DeBaun et al, 2005), an objectoriented, component-based architecture is designed, built on which a black oil simulator and a compositional simulator are developed.…”
Section: Introductionmentioning
confidence: 99%